2014
DOI: 10.14214/sf.1077
|View full text |Cite
|
Sign up to set email alerts
|

Recent browsing damage by moose on Scots pine, birch and aspen in young commercial forests – effects of forage availability, moose population density and site productivity

Abstract: Recent browsing damage by moose on Scots pine, birch and aspen in young commercial forests -effects of forage availability, moose population density and site productivity Bergqvist G., Bergström R., Wallgren M. (2014). Recent browsing damage by moose on Scots pine, birch and aspen in young commercial forests -effects of forage availability, moose population density and site productivity. Silva Fennica vol. 48 no. 1 article id 1077. 13 p. Highlights• Moose damage was most common on aspen and least common on Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…Moose cause damage to trees by browsing apical shoots, lateral twigs and foliage, breaking the main stem and peeling the bark. Severe damage may lead to a reduction of the technical quality of timber, growth losses and impaired development of the stand (e.g., Heikkilä and Härkönen 1993;Heikkilä and Löyttyniemi 1992;Härkönen et al 2009;Bergqvist et al 2001Bergqvist et al , 2003Bergqvist et al , 2014. The biggest economic losses to forestry by moose are due to winter time browsing in Scots pine (Pinus sylvestris L.) sapling stands in Fennoscandia (Helle et al 1987;Lavsund 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Moose cause damage to trees by browsing apical shoots, lateral twigs and foliage, breaking the main stem and peeling the bark. Severe damage may lead to a reduction of the technical quality of timber, growth losses and impaired development of the stand (e.g., Heikkilä and Härkönen 1993;Heikkilä and Löyttyniemi 1992;Härkönen et al 2009;Bergqvist et al 2001Bergqvist et al , 2003Bergqvist et al , 2014. The biggest economic losses to forestry by moose are due to winter time browsing in Scots pine (Pinus sylvestris L.) sapling stands in Fennoscandia (Helle et al 1987;Lavsund 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Markgren 1970;Lavsund 1987;Bergqvist et al 2014). For example, National Forest Inventory (NFI) shows moose damage in almost one million hectares in Finland (Korhonen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the total number of deciduous trees on a plot increased the probability of browsing, but when the number of deciduous trees taller than pines was added to the model, the effect of the total number of deciduous trees was overridden. Overtopping deciduous trees have been detected to increase the browsing of pines in earlier studies as well (Heikkilä 1990;Bergqvist et al 2014). The mechanism behind this has been attributed to the shading effect of tall deciduous trees on pines which may affect either the structural characteristics of pines, by making the trunk and shoots slender, or shading might change the proportions of chemical compounds in the trees more favourable for moose (Edenius 1993).…”
Section: Study Imentioning
confidence: 93%
“…In most of the studies, deciduous trees either did not increase the browsing of pines or the increase was slight (Heikkilä 1990;Edenius 1991;Härkönen et al 1998;Bergqvist et al 2012;Bergqvist et al 2014), while some studies have found a positive effect between most favoured deciduous species and pine browsing Milligan and Koricheva 2013). According to the stand level models in I, the number of deciduous trees did not predict the proportion of browsed pines to increase when the average number of deciduous trees was used.…”
Section: Study Imentioning
confidence: 99%
See 1 more Smart Citation